The role of IL‐23/IL‐17 axis in human kidney allograft rejection. Issue 6 (19th July 2018) - Haouami, Youssra; Dhaouadi, Tarak; Sfar, Imen; Bacha, Mongi; Gargah, Tahar; Bardi, Rafika; Abderrahim, Ezzeddine; Goucha, Rym; Ben Abdallah, Taïeb; Gorgi, Yousr
ABSTRACT: Th17 cell subset has been implicated in autoimmune diseases, tumor immunity and, transplant rejection. In order to investigate the role of IL‐17/IL‐23 pathway in allograft outcome, intragraft expression of IL‐17 mRNA and single nucleotide polymorphisms (SNPs) of IL‐17A, IL‐17F, IL‐17RC, and IL23R genes were evaluated with a quantification of IL‐17A, IL‐17F, and IL‐23 plasma levels. This study revealed that recipients with acute rejection (AR) had a significant increase in IL‐17A mRNA expression levels after transplantation compared to controls ( P = 0.037). Moreover, IL‐17A plasma levels were significantly higher in AR group; pretransplantation (Day–1 [D–1]): P = 0.00022 and posttransplantation (Day 7 [D7]): P < 10 –14 . IL‐17F and IL‐23 plasma levels were significantly higher in AR at D7 only (47.86 vs. 22.99 pg/ml; and 33.82 vs. 18.811 pg/ml; P = 0.015 and P < 10 –17, respectively). Using receiver‐operating characteristic curves, D7 IL‐17A and IL‐23 plasma levels exhibited excellent sensitivities and specificities for predicting AR. Genetic study revealed no association between IL‐17A, IL‐17F, IL‐17RC, and IL23R studied SNPs and AR. Nevertheless, a significant improvement of graft survival was found in kidney transplant recipients carrying IL‐17F‐rs763780*A/A, IL‐17RC*G/G, and *G/A genotypes. Besides, IL‐17A mRNA levels were significantly higher in patients carrying the IL‐23R*G/G genotype comparatively to those with *G/A genotype. Based on these findings, significant increase of IL‐17A mRNA and protein levels in AR recipients that are genetically controlled highlights the role of this cytokine that can be a useful clinical biomarker to predict early acute renal allograft rejection. Abstract : Study showing significant associations between Day 7 plasma IL‐17A, IL‐17F and IL‐23 and AR with good performances for IL‐17A and IL‐23 in predicting acute rejection (AR) occurrence; significant increase of IL‐17A expression in kidney graft in case of AR; a significant improvement of graft survival in recipients carrying IL‐17F‐rs763780*A/A, IL‐17RC*G/G and *G/A genotypes.